Do Liquidation Values Affect Financial Contracts? Evidence from Commercial Loan Contracts and Zoning Regulation - Benmelech, E.; Garmaise, M. J.; Moskowitz, T. J. (Quarterly Journal of Economics, 2005)
We examine the impact of asset liquidation value on debt contracting using a unique set of commercial property loan contracts. We employ commercial zoning regulation to capture the flexibility of a property's permitted uses as a measure of an asset's redeploy ability or value in its next best use. Within a census tract, more redeployable assets receive larger loans with longer maturities and durations, lower interest rates, and fewer creditors, controlling for the property's type, sale price, and earnings-to-price ratio. These results are consistent with incomplete contracting and transaction cost theories of liquidation value and financial structure.